(untitled) (مجلة إحالات, 2026)
The cultural history of the city of Nedroma bears witness to this cultural, artistic, scientific and even literary dynamism in the city, given what we see in the books of biographies and translations of the notables of the central Maghreb, of stopping at many literary, scientific and political names that grew up in the city and were affiliated with it. And since this was the case, it was necessary for masters of speech and masters of the horizons of poetic creativity to graduate from this cultural momentum. In the field of Malhoun poetry, those working on this art studied the texts of one of the city’s most famous poets, Sheikh Qaddour bin Ashour Al-Zarhouni, who is considered the most famous and prolific poet in the city. He has been the subject of many studies, especially after the publication of his collection of poems, which was compiled by Muhammad bin Amr Al-Zarhouni. However, many names remained forgotten and on the margins of work, and their texts were not collected or verified, including Sheikh Muhammad al-Ruma’un, who is considered the dean of Malhun poetry in the city. We are trying to remove the veil of marginalization from him as a name and as a text through this research paper that seeks to introduce him and his texts.